Youtube as a resource for improvement and learning in teacher education - Silva, Naysa Christine Serra; Chahini, Thelma Helena Costa (Seven Editora, 2024)
This study aims to investigate the relevance of Youtube as a resource for learning and improvement in teacher training, based on the application of a questionnaire containing open and closed questions with teachers in training at the undergraduate and graduate levels enrolled in courses at the Federal University of Maranhão. the studies by Kenski (2012), Garcia et al. (2011), Silva (2021), Silva and Chahini (2020), among others. The methodology developed is characterized by qualitative approach; and descriptive and exploratory as to the object. This research was developed via digital technologies from rapid communication applications with the participation of 22 teachers in training in the various areas offered by the Federal University of Maranhão, from March to July 2023. The data obtained show that the YouTube platform provides teachers with significant elements in their professional training. DOI:https://doi.org/10.56238/sevened2024.007-062